Green and Blue Infrastructures and Nature-Based Solutions to Reduce Pollutant Emissions and Make Transitioning Urban Ecosystems More Climate Change-Adaptive - Quattrone, Giuliana (Green Building & Construction Economics, 2023)
The growing impact of extreme weather phenomena in different areas of the globe and the empirical evidence of the economic, social and environmental damage caused by global warming, urgently, calls for appropriate responses. Urban areas are part of the planet where the greatest social costs of global warming will be paid, and so it seems very important to take on the issue of climate change adaptation in land use and urban planning. In several cities, new planning instruments and projects have been developed that highlight a profound cultural change and approach to urban planning that we have known for the last two centuries. The lack of adequate management measures concerning increasingly frequent disasters lead to environmental, economic (e.g., exposure to risks and costs associated with extreme weather events), and social impacts (e.g., health impacts related to air quality, heat islands, etc., with an increase in chronic ailments and various diseases). As recognised by Sustainable Development Goal 11 (SDG11), the United Nations (UN) New Urban Agenda and the World Forum on Urban Forests, green and blue infrastructures (GBIs) and nature-based solutions (NBSs) can reduce these impacts by promoting population health shaping as an adaptation strategy to climate change. GBIs and NBSs for the sustainability, resilience and well-being of urban communities are increasingly considered efficient strategies to mitigate climate change-dependent disasters, but they are not yet considered in a systematic way within urban planning. The paper aims to investigate the role of GBIs and NBSs in the resilience of cities and urban communities against the risks associated with the climate crisis. Furthermore, the paper suggests how GBI and NBS could be interwoven into visions, urban planning, and design to create resilient places for people and resilient community behaviours.